2022
DOI: 10.1002/ase.2218
|View full text |Cite
|
Sign up to set email alerts
|

Promoting metacognition in an allied health anatomy course

Abstract: Metacognition, the ability to self‐regulate one's learning and performance, has been shown to improve student outcomes. Anatomy is recognized as one of the toughest courses in allied health curricula, and students could benefit from metacognitive activities. The purpose of this study was to explore the changes in metacognition of allied health students in an anatomy course and identify which groups need support with this skill. First‐year physician assistant (MPAS), physical therapy (DPT), and occupational the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Conversely, repeating students often committed to a particular study strategy until they received feedback in the form of their examination scores, and even then, the students opted to enhance the existing strategy rather than switching to something different. This "doubling down" on a familiar study strategy rather than exploring other potential strategies has been previously documented in allied health students (Cale et al, 2023). As stress and fatigue mounted, the allied health students preferred to rely on familiar but less effective strategies because they lacked the time to risk exploring new strategies.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Conversely, repeating students often committed to a particular study strategy until they received feedback in the form of their examination scores, and even then, the students opted to enhance the existing strategy rather than switching to something different. This "doubling down" on a familiar study strategy rather than exploring other potential strategies has been previously documented in allied health students (Cale et al, 2023). As stress and fatigue mounted, the allied health students preferred to rely on familiar but less effective strategies because they lacked the time to risk exploring new strategies.…”
Section: Discussionmentioning
confidence: 76%
“…This introduces the students to the practice of metacognitive reflection early in their education but limits our ability to determine if or how metacognitive ability and exam preparation strategies change over subsequent exams. Future iterations of the PBLI could be deployed after subsequent Human Structure exams to encourage students to continue the practice of metacognitive reflection as well as facilitate longitudinal data collection on student metacognition and exam preparation strategies.However, work completed by the authors has found that students are most receptive to changes in their learning strategies early on within a professional medical course, with little change occurring following subsequent exams, which supports the placement of the PBLI activity within this curriculum(Cale et al, 2023). More broadly, several other factors may have also contributed to a student's likelihood of struggling in Human Structure and medical school as a whole, such as an URiM background or a lack of laboratory-based anatomy experience.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Effective communication is integral for clinical reasoning involving critical questioning, interdisciplinary collaboration, and patient involvement [ 32 ]. Participants were cognizant of all these aspects; however, prompts by the facilitators were needed to improve the interprofessional discussions.…”
Section: Resultsmentioning
confidence: 99%
“…It is already well evidenced that students are not particularly good at regulating their own study behaviors, or time on task when combinations of resources are offered (Naumann, 2019). Therefore, it is the responsibility of educators to support them through hybrid teaching reforms by offering students effective metacognitive strategies on how to use and integrate their resources effectively with face‐to‐face components (McCabe, 2011; Cale et al., 2023). By developing digital tools where the cognitive demands are known (through the instructional design process), educators can make conscious decisions on aspects such as designing dual code over single code presentations or considering the impact of low interest versus high interest detail.…”
Section: Discussionmentioning
confidence: 99%